Analysis Of The Sensory Quality Of Rolled Cake Using Coconut Milk Fat - Rahmadani, Fitri; Siregar, Juliana; Kasmita, Kasmita; Yasih, Fitri (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This research was motivated by the high trans fat content in margarine which is associated with an increased risk of heart disease and there has been no research on the effect of using coconut milk on the quality of rolled sponge cake. This research aims to analyze the effect of the use of fat (margarine, coconut milk) on the quality of rolled sponge cake which includes shape, volume, color, aroma, texture and taste. The type of research carried out was experimental, namely conducting direct experiments on the effect of the use of fat (margarine, coconut milk) on the quality of rolled sponge cake and repeated three (3) times. The data collection technique in this research is an organoleptic test on the quality of rolled sponge cake in terms of (shape, volume, color, aroma, texture and taste. The data analysis technique uses statistical analysis of the mean difference test (t test). The results of the research were the quality of the neat shape with a diameter of 5-7 in both treatments, the quality of the skin color being brownish yellow in both treatments, the quality of the volume expanding (with a sponge height of 3 cm) in both treatments, the quality of the inner color being yellow in rolled cakes using margarine and not yellow in rolled sponge cake using coconut milk, fragrant aroma quality in both treatments, soft texture quality (when pressed back to its original shape with a height of 3 cm) in both treatments, sweet texture quality in rolled sponge cake using margarine and not sweet in sponge cake rolls that use coconut milk. In this research, there was a significant influence on the quality of the inner color and taste of the rolled sponge cake.This research was motivated by the high trans fat content in margarine which is associated with an increased risk of heart disease and there has been no research on the effect of using coconut milk on the quality of rolled sponge cake. This research aims to analyze the effect of the use of fat (margarine, coconut milk) on the quality of rolled sponge cake which includes shape, volume, color, aroma, texture and taste.The type of research carried out was experimental, namely conducting direct experiments on the effect of the use of fat (margarine, coconut milk) on the quality of rolled sponge cake and repeated three (3) times. The data collection technique in this research is an organoleptic test on the quality of rolled sponge cake in terms of (shape, volume, color, aroma, texture and taste. The data analysis technique uses statistical analysis of the mean difference test (t test). The results of the research were the quality of the neat shape with a diameter of 5-7 in both treatments, the quality of the skin color being brownish yellow in both treatments, the quality of the volume expanding (with a sponge height of 3 cm) in both treatments, the quality of the inner color being yellow in rolled cakes using margarine and not yellow in rolled sponge cake using coconut milk, fragrant aroma quality in both treatments, soft texture quality (when pressed back to its original shape with a height of 3 cm) in both treatments, sweet texture quality in rolled sponge cake using margarine and not sweet in sponge cake rolls that use coconut milk. In this research, there was a significant influence on the quality of the inner color and taste of the rolled sponge cake.